A prospective, randomized study of tissue adhesive Versus standard wound closure technique for Laparoscopic abdominal procedure - Ali, Nor Huda Mat (2007)
To compare the effecti veness of cyanoacrylate ti ssue adhes ive vv ith convent ional suture in closing laparoscopic abdominal incision. Design: Prospecti ve, randomized controlled study Setting: Gynaecology ward of Hospital Tengku Ampuan Afzan. Kuantan from April 2005 ti ll November 2006. Participants: 64 patients for laparoscopi c abdominal procedure Methodology: Pati ents were chosen based on inclusion and exclusion criteria . They were then randomly assigned to recci\"C either ti ssue adhesi\·e or suture.